Biodiversity, Abundance and Seasonal Fluctuation of Ground Beetles on Massa Region - Belhassan, Eman M A.; Bataw, Ali A.; Attia , Mansour Salem A. (Al-Mukhtar Journal of Sciences, 2018)
The present study was carried out to investigate the biodiversity, abundance and seasonal fluctuation of ground beetles on Massa region from June 2015 to October 2016. The beetles were collected using 20 pitfall traps which were operated on a weekly basis, a total of 2867 specimen representing two families Carabidiae and Tenbrionidae and 10 genera (Blaps polychresta, Zophosis punctata, Pimelia interpunctata, Blaps nitens, Adesmia dilatata, Scaurus vicinus, Tentyria cyrenaica, Laemostenus complanatus, Ditomus cilpeatun and Akis costitubera were recorded. Overall diversity was 81% and 83% Simpson's scale and Shannon's scale respectively. The highest index; 0.116841 (Simpson's index) and 0.36693 (Shannon's index) was found in species Z. punctata. Results showed the influence of temperature on A. costitubera, B. polychresta and D. cilpeatun with the A. costitubera being a better predictor, addition to constant of A. costitubera Beta =0.818 ; constant of A. costitubera and B. polychresta Beta = 0.625 and 0.53 and constant of A. costitubera , B. polychresta and D. cilpeatun Beta = 0.629 , 0.335 and 0.191. The results concluded the importance of using ecological indexes in studying the abundance and seasonality of ground beetles fluctuated during different seasons.